2016
DOI: 10.1177/0021934716678392
|View full text |Cite
|
Sign up to set email alerts
|

Leadership for Africa’s Development

Abstract: The African continent remains at the periphery in world affairs, as many have argued. Similarly, many scholars have advanced cogent reasons for this unfortunate reality. The development of the continent is also unimpressive, relative to the potential of the African economies. It is therefore important that Africa pursues its own socioeconomic development approach instead of what appears to be inappropriate policies that are being implemented in most if not all African countries, as argued elsewhere. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…There has been much debate about the influence of colonialism on traditional leadership ideals in Africa, with a call for effective leadership in this post-colonial era (Adeyemi, 2017;Bikoko, 2007;Blake, 2005;Bolden & Kirk, 2009;Bulhan, 2015;Mathooko, 2013). Some argue for a return to indigenous Afrocentric leadership ideals (Bolden & Kirk, 2009;Bulhan, 2015;du Preez, 2012;Eyong, 2017;Gumede, 2017). On the other hand, implying that they had adopted some Western leadership ideals recommended by Jallow (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much debate about the influence of colonialism on traditional leadership ideals in Africa, with a call for effective leadership in this post-colonial era (Adeyemi, 2017;Bikoko, 2007;Blake, 2005;Bolden & Kirk, 2009;Bulhan, 2015;Mathooko, 2013). Some argue for a return to indigenous Afrocentric leadership ideals (Bolden & Kirk, 2009;Bulhan, 2015;du Preez, 2012;Eyong, 2017;Gumede, 2017). On the other hand, implying that they had adopted some Western leadership ideals recommended by Jallow (2014).…”
Section: Discussionmentioning
confidence: 99%
“…From an educator's point of view, providing opportunities for interaction between students has previously been seen as an integral aspect of online courses in contributing to online learning success, but the opinions of the online Furthermore, this research aims to examine if these differences exist, do they support previous findings in the European and American studies, or were there variances influenced by the unique cultural context (Beldarrain, 2006;Keeney et al, 2017;Palloff & Pratt, 1999)? It will consider if the perceived leadership qualities reported by students and lecturers reflect Western or Afrocentric ideologies or a combination of both (Bulhan, 2015;Gumede, 2017;Smedick & Rice, 2018). In addition, it addresses some challenges presented in online learning platforms at PAC University in Kenya.…”
Section: Leadership In An Africanmentioning
confidence: 99%
“…The leadership philosophy of Ubuntu as a practice has received attention in research as a key consideration to determining what leadership in Africa entails (Grobler & Singh, 2018;Le Grange, 2011;Muchiri, 2011;Nzimakwe, 2014), although very little empirical research has been conducted on the concept to determine its effectiveness in leadership practice (Brubaker, 2013). Gumede (2017), Mbigi (2000) and Van Rensburg (2013) stated similar sentiments along the lines that African leadership is grounded on Afrocentric histories, philosophies, epistemologies and other pan-Africanist ideologies within the evolving African cultures. Metz (2018, p. 42) also talks about an Afro-communal ethic type of leadership, which is unique to Africa, based on the belief that 'one should relate communally'.…”
Section: African Leadershipmentioning
confidence: 97%
“…Esteemed authors, such as Mbeki (2005), Mbigi (2007), Mutwa (2019) and Mutwa and Larsen (1996), have also dedicated their focus and work on ideological and political matters on the subject of leadership. Notably, several researchers reported that very little academic research has been conducted towards understanding leadership in Africa (Amah, 2019;Cerff, 2017;Gumede, 2017;Kuada, 2010;Walumbwa et al, 2011).…”
Section: African Leadershipmentioning
confidence: 99%
“…Gumede argues that thought liberation and critical consciousness have the potential to achieve a decolonised form of leadership. Additionally, Gumede (2017) contends that raising critical consciousness among Africans involves an endeavour to "deconstruct and reconstruct their sense of being". Gumede opines, "Critical consciousness in particular implies a thorough understanding of the obtaining reality and the ability to take fitting action to address the oppressive elements of that reality, as Paulo Freire (2005) had put it".…”
Section: Conscious Leadership Critical Consciousness and Decolonisedmentioning
confidence: 99%